Dampak Sistem Pengendalian Internal Terhadap Penagihan Piutang Di Kota Bandung - Khaerul Umam; Angga Eka Pratama (Publica: Jurnal Pemikiran Administrasi Negara, 2018)
This research is in the background behind the problems of Bandung City, which for the past five years still have a reasonable opinion with exceptions, one of the reasons is the high level of accounts receivable at the Bandung City Financial and Asset Management Agency every year, and billing is less effective every year. receivables for leasing land and buildings in the city of Bandung. This study aims to determine the internal control system on the effectiveness of receivables collection in Bandung City BPKA and the magnitude of the influence of the dimensions of the internal control system on the effectiveness of receivables collection in Bandung City BPKA partially and simultaneously. The research used in this study is associative research with a quantitative approach because it aims to determine the effect of the internal control system on the effectiveness of accounts receivable collection at the Bandung City Financial and Asset Management Agency. Data collection uses literature studies, documentary studies and questionnaires on apparatus in Bandung City BPKA. Data analysis techniques are carried out using the correlation coefficient of determination, simple linear regression analysis and t (t-test).